2002
DOI: 10.1016/s0309-1740(02)00127-4
|View full text |Cite
|
Sign up to set email alerts
|

Meat tenderness and muscle growth: is there any relationship?

Abstract: Our objectives for this manuscript are to review the mechanisms of muscle growth, the biological basis of meat tenderness, and the relationship between these two processes. Muscle growth is determined by hyperplasia and hypertrophy. Muscle cell size is determined by the balance between the amount of muscle protein synthesized and the amount of muscle protein degraded. Current evidence suggests that the calpain proteolytic system is a major regulator of muscle protein degradation. Sarcomere length, connective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
1
23

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(222 citation statements)
references
References 42 publications
6
185
1
23
Order By: Relevance
“…The calpain-calpastatin system regulates protein degradation in animals premortem and postmortem (Koohmaraie et al, 2002). The 4 markers were SNP within genes controlling the calpain-proteolytic system, specifi cally calpastatin (CAST; Barendse, 2002), calpain 3 (CAPN3; Barendse et al, 2008), and μ-calpain 1 (CAPN1-4751 and CAPN1-316; White et al, 2005 andPage et al, 2002, respectively).…”
Section: Experimental Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calpain-calpastatin system regulates protein degradation in animals premortem and postmortem (Koohmaraie et al, 2002). The 4 markers were SNP within genes controlling the calpain-proteolytic system, specifi cally calpastatin (CAST; Barendse, 2002), calpain 3 (CAPN3; Barendse et al, 2008), and μ-calpain 1 (CAPN1-4751 and CAPN1-316; White et al, 2005 andPage et al, 2002, respectively).…”
Section: Experimental Designsmentioning
confidence: 99%
“…Consumers consistently rate tenderness as the most important contributor to beef palatability in Australia (Egan et al, 2001) and the United States (Koohmaraie et al, 2002). Favorable genetic markers have been shown to improve shear and compression force measurements of tenderness (Cafe et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing the interaction between protein turnover and eating quality, Koohmaraie et al (2002) proposed that if in part an increase in net protein in the live animal was achieved by a decrease in protein turnover (i.e. as a function of increased calpastatin activity in the muscle), this would reduce post-mortem aging rates, resulting in tougher meat.…”
Section: Introductionmentioning
confidence: 99%
“…In experiment 1, the balanced numbers of samples for most muscles aged 7 and 21 days showed that aging rates varied between the different muscles. Koohmaraie et al (2002) proposed that the major contributors to variation in tenderness within a muscle included the rate of proteolysis, sarcomere length and connective tissue. Increased sarcomere length impacts aging rates by causing an initial increase in tenderness with slower subsequent ageing, so that ultimately tenderness scores in stretched and unstretched muscle converge (Tornberg 1996).…”
Section: Discussionmentioning
confidence: 99%